2006
DOI: 10.1038/modpathol.3800482
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular features of colorectal carcinoma with signet ring cell component and colorectal carcinoma with mucinous component

Abstract: Signet ring cell carcinoma and mucinous carcinoma are distinct subtypes of colorectal adenocarcinoma. The morphologic and molecular spectra of colorectal carcinomas with various signet ring cell components and colorectal carcinomas with various mucinous components, compared to non-mucinous adenocarcinomas, have not been examined. The study groups consisted of 39 carcinomas with various signet ring cell components ('the signet group'), 167 carcinomas with various mucinous components ('the mucinous group'), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
250
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(277 citation statements)
references
References 31 publications
24
250
3
Order By: Relevance
“…25,28,44 BRAF V600E mutation occurs in the majority of sporadic colorectal cancers with high-level microsatellite instability and in 5-20% of microsatellite status colorectal cancers. In this study, BRAF V600E mutation was identified in one-third of signet ring cell carcinomas, which is comparable to the 22% figure reported by Ogino et al 35 BRAF V600E mutation in our series has strong correlation with CpG island methylation phenotype-positive status, but not with any clinicopathologic or molecular features. Several studies have shown that BRAF V600E mutation does not affect prognosis in colorectal cancers with high-level microsatellite instability, but adversely affects survival in microsatellitestable colorectal cancers.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…25,28,44 BRAF V600E mutation occurs in the majority of sporadic colorectal cancers with high-level microsatellite instability and in 5-20% of microsatellite status colorectal cancers. In this study, BRAF V600E mutation was identified in one-third of signet ring cell carcinomas, which is comparable to the 22% figure reported by Ogino et al 35 BRAF V600E mutation in our series has strong correlation with CpG island methylation phenotype-positive status, but not with any clinicopathologic or molecular features. Several studies have shown that BRAF V600E mutation does not affect prognosis in colorectal cancers with high-level microsatellite instability, but adversely affects survival in microsatellitestable colorectal cancers.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we analyzed the molecular features of 33 resected signet ring cell carcinomas and explored their correlation with outcome. High-level microsatellite instability has been reported in 25-31% of signet ring cell carcinomas, 15,35 which is similar to the 24% figure observed in this series. High-level microsatellite instability is a marker of favorable outcome in sporadic colorectal cancer, but does not favorably influence survival in signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations